Is Poland Ready for Inflation Targeting? - Christoffersen, Peter; Westcott, Robert (Washington, D.C. : International Monetary Fund, 1999)
Monetary policymakers in advanced transition economies such as Poland are increasingly interested in how inflation responds to changes in policy instruments and other economic forces. In this paper, measures of underlying CPI inflation based upon optimal trimming concepts are developed. The sensitivity of these CPI measures to changes in a set of 25 policy and economic variables is then studied via Granger causality tests and impulse responses and a multivariate model of CPI inflation developed. The results show that a core set of variables characterize one-period-ahead underlying inflation moderately well but that statistical linkages are not yet robust.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet